Meningkatkan Nilai Spiritual Anak Melalui Mengaji Sore di Desa Batu Raja Kecamatan Pondok Kubang Kabupaten Bengkulu Tengah - Puput, Elpa Okti; Putra Pratama, Alib; Diana Sari, Siska; Risna; Elpa Okti Saputri; Rindang Septiana; Camela Bella; Trisna Komala Putri; Sesi Kuslinawati; Nanda Gusti Lestari; Muhammad Fajar; Yusuf Kholid Akbar; et al. (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
The afternoon Koran activity in Batu Raja Village, Pondok Kubang District, Central Bengkulu Regency, is an initiative aimed at improving children's spiritual values through Al-Qur'an education. This research explores the contribution of the program to children's spiritual development, as well as the challenges faced and recommendations for its development in the future. The research results showed that the evening Koran activity significantly increased children's awareness of worship and understanding of ethics and morals. However, there are challenges such as changes in children's interests due to the influence of technology, limited human resources, and inadequate facilities. The proposed recommendations include increasing training for ustadz, improving physical facilities, collaborating with local governments and educational institutions, as well as developing additional activities to attract children's interest. By implementing these recommendations, it is hoped that the evening Koran program can continue to develop and have a wider positive impact in forming children's religious character and strengthening the spiritual foundations of society.